Design of Log Periodic Dipole Array Antenna Ranging from 30 to 150 MHz - Subedi, Upendra; Nepal, Rabin; Lwagun, Rhimesh; Rijal, Sanjay (Journal of Innovations in Engineering Education, 2020)
This paper describes construction of 16 element frequency independent and high bandwidth Log Periodic Dipole Array antenna which works within the frequency range of 30 to 150 MHz. The antenna of gain 8 dBi is designed by calculating the parameters from Matlab. Matlab program is used to calculate the parameters like length of elements, separation between elements, theoretical impedance, standing wave ratio, etc. Thus, the designed antenna was fabricated. The antenna element is a cylindrical aluminum pipe of diameter 9mm and the boom used is rectangular antenna pipe of dimension 1”X1”. Fabrication also includes other materials like M-seal, zip tie, etc for physical stability of the antenna. Log Periodic Dipole Array antenna design described in this paper is fed with 75 ohm coaxial cable to 1:1 balun. Balun is also used for impedance matching between the antenna and coaxial cable. Antenna analyzer is used to measure Standing Wave Ratio and Impedance which are found to be 1.623 and 71.5625 ohm respectively. The antenna can be a receiver or a transmitter type for operating with the signals within Very High Frequency band.